Integrasi PBL dan Media Berbasis AI dalam Pengajaran Fikih Mawaris: Upaya Meningkatkan Kemampuan Berpikir Kritis Mahasiswa - Wahab, Abdul (Indo-MathEdu Intellectuals Journal, 2025)
Critical thinking was recognized as a crucial competency in higher education, yet the instruction of Islamic inheritance law (fikih mawaris) had often relied on conventional approaches with minimal analytical engagement. This study aimed to investigate the effectiveness of integrating Problem-Based Learning (PBL) with artificial intelligence (AI)-based media in improving students’ critical thinking skills. A quasi-experimental design was employed involving three groups: an experimental group (PBL + AI), a positive control group (PBL only), and a negative control group (traditional lecture), with participants drawn from Muhammadiyah University of Mamuju. Data were collected through a critical thinking test developed using Zubaidah’s rubric and analyzed using ANCOVA. The results showed a statistically significant difference among the groups. The experimental group obtained a significantly higher than both control groups. These findings suggested that the integration of AI-based media into PBL effectively enhanced students' critical thinking in the context of fikih instruction. The study implied a pedagogical shift in Islamic education toward technology-supported learning while maintaining ethical and epistemological integrity.